Tightly-coupled GIS data in GNSS fix computations with integrity testing. (15th May 2008) - Fouque, C.; Bonnifait, Ph.
Global Navigation Satellite Systems (GNSS) are often used to localise a receiver with respect to a given map. This association problem, also known as map-matching, is usually addressed using estimated positions computed by the GNSS receiver. In this paper we propose a method that combines the cartographic data in the GNSS computation fix itself. We focus on the use of a road network provided by cartographers such as NavTeQ or TeleAtlas. Geo-referenced data is modelled by segments that can be used as constraints or fused with the pseudo-ranges. Using residuals, a new method for tackling the underlying problem of the road selection is proposed. We show that this approach is also well adapted to the integrity problem of map-matching, since a consistency test is derived. Experimental results illustrate the performance of this method with different maps.